Modelling on Tracking Test Condition of Polymer Nanocomposite using Finite Element Simulation - Fatin Liyana Muhamedin; M. A. M. Piah; Nordiana Azlin Othman (Universitas Ahmad Dahlan, 2015)
Electrical tracking is a formation process of a permanent conducting path across the insulating material due to surface erosion under high voltage stress. The existing of leakage current (LC) on the wet contaminated material surface causes the generation of surface discharges that resulted in the material degradation. The effects of electric field distribution and current density on LLDPE-Natural Rubber blends material were investigated using finite element method (FEM) analysis. In this paper, a variety of physical parameters particularly contaminant flow rate, various applied voltages, material properties of permittivity and conductivity were studied when nanofiller is added to LLDPE-Natural rubber blend. The simulation works using FEM software of Quickfield was applied to the tracking test condition of IEC 60587 standard. The results show that the electric field distributions are critical on the edges of contaminant solution path at higher voltage level. The current density and electric field distribution is increase with higher applied voltage. The polymer nanocomposite with 1-5 % of nanofiller exhibits a good resistance to tracking and erosion test.